Respuesta :

f(x)=3x^2-x

[tex]\\ \rm\longmapsto f(-2)[/tex]

[tex]\\ \rm\longmapsto 3(-2)^2-(-2)[/tex]

[tex]\\ \rm\longmapsto 3(4)-(-2)[/tex]

[tex]\\ \rm\longmapsto 12-(-2)[/tex]

[tex]\\ \rm\longmapsto 12+2[/tex]

[tex]\\ \rm\longmapsto 14[/tex]

Space

Answer:

14

Step-by-step explanation:

f(x) = 3x² - x

To find f(-2), substitute -2 for x into the function f.

  • f(-2) = 3(-2)² - (-2)

Now, use PEMDAS to evaluate the function.

Start by evaluating the exponent.

  • f(-2) = 3(4) - (-2)

Next, multiply 3 and 4 and -2 by -1.

  • f(-2) = 12 + 2

Add the two terms together.

  • f(-2) = 14

The correct answer is f(-2) = 14.

ACCESS MORE